Vocabulary learning autonomy through incorporation of English songs: Indonesian EFL students' perspectives - Lestari, Ika Wahyuni; Nuri Hardiyanti (Penerbit Universiti Kebangsaan Malaysia, 2020)
English songs have been widely used by learners as a medium to learn vocabulary. This qualitative study explored Indonesian students' experiences in using English songs as a medium to learn vocabulary autonomously outside in-class learning. Data were collected through in-depth interview to four second-year English Department students who reported using English songs to help them acquire vocabulary autonomously. The results of the interview showed that the participants preferred slow beat tempo of songs to obtain clear understanding on the words used in the songs. They also reported that the decision to use English songs was driven by their needs to the exposures of authentic and contextual English lexicons, the representations of learners' feelings and emotions through songs, the sense of enjoyable atmosphere songs created, and vocabulary retention. While listening to English songs, cognitive and metacognitive strategies were also applied by the participants to help them acquire vocabulary more effectively. At last, the study was concluded by proposing teachers' roles to enhance learners' autonomy in vocabulary learning through English songs.